Test Anxiety During Formative Assessment in English Learning: Insights from Islamic Boarding School Students - Bukhori, Bukhori; Herlinda, Silvi; Putriani, Zelly; Maulana, M.Faisal; Haq, Muhammad Valiyyul (Al-Manar, 2025)
This study investigates test anxiety among students at Aek Hayuara Sibuhuan Islamic Boarding School during formative assessments in English learning and explores the factors contributing to their anxiety. Employing a qualitative case study approach, the research selected participants through purposive sampling. Data collection methods included closed-ended questionnaires and interviews. The findings reveal that the majority of students experience test anxiety, which manifests in two key dimensions: emotionality and worry. Furthermore, four primary factors contribute to this anxiety: fear of failing the course, psychological distress, poor study skills, and low self-esteem.